A Mg2+-Ge4+ substituting strategy for optimizing color rendering index and luminescence of YAG: Ce3+ phosphors for white LEDs. (February 2018) - Jiang, Lipeng; Zhang, Xiyan; Tang, He; Zhu, Shiqi; Li, Qingxi; Zhang, Wenmin; Mi, Xiaoyun; Lu, Liping; Liu, Xiuling
Graphical abstract: Highlights: Mg 2+ -Ge 4+ ion pairs can partially substitute the Al 3+ ions of YAG successfully. With the substitution, the garnet crystal structure remains unchanged. With increasing Mg 2+ -Ge 4+ ions concentrations, the emission spectra show a progressive red-shift, from 528 to 552 nm (about 24 nm). In white LEDs, with increasing Mg 2+ -Ge 4+ ions concentrations, the CCT decreased gradually from 6798 to 3261 K and the CRI increased from 76.5 to 89.3. Abstract: Mg 2+ -Ge 4+ ions substituted YAG: Ce 3+ phosphors (Y3 Al5-2x Mgx Gex O12 : Ce 3+ ) were prepared by high temperature solid state reaction method. X-ray diffraction (XRD), Scanning election microscope (SEM), Photoluminescence (PL) spectra and so on were used to characterize the samples. The effects of Mg 2+ -Ge 4+ concentrations on the morphology, structure, luminescence properties, fluorescence lifetime and white LED performance of YAG: Ce 3+ phosphors were studied in detail. The results indicate that Mg 2+ -Ge 4+ ion pairs can partially substitute the Al 3+ ions of YAG successfully. With the substitution, the garnet crystal structure remains unchanged. However the emission spectra show a progressive red-shift, from 528 to 552 nm (about 24 nm). The lifetime decreased rapidly from 84 to 26 ns. In particular, the correlated color temperature (CCT) decreases gradually from 6798 to 3261 K and the color rendering index (CRI) increases from 76.5 to 89.3 with the increasing of the incorporation content of Mg 2+ -Ge 4+ ion pairs.